The Italian validation of the University Student Engagement Inventory - Esposito, Giovanna (2022)
Student Engagement (SE) refers to the extent to which a student participates in academic and non-academic activities, invests in and commits to learning, belonging and identification with the educational institution. Despite the relevance of SE for students’ success, a few valid and reliable instruments have been developed. This study presents the Italian validation of the University Student Engagement Inventory (USEI), which adopts both a 3 first-order conceptualization of the SE and a secondorder construct (engagement). The paper reports the psychometric analyses (test–retest reliability, construct, convergent, discriminant validities, internal consistency) on a validation sample of 628 Italian university students from 2 areas of study (psychology and biology). Criterion validity was assessed in relation to students’ drop-out intention, academic achievements, Grade Point Average (GPA) and motivation. Invariance analysis was performed for gender and area of studies. Results showed that the USEI presented a good test–retest reliability and factorial construct validity (both for the three-factor and one-factor models), it positively predicted students’ academic motivation, GPA and academic achievements, and negatively intention to drop out. The results indicate that the USEI can produce valid data on SE in the Italian context and may have implications for assessing SE and implementing intervention programs.